Examining EFL Student Response to Student-Centered Classroom Instruction - Juliaty, Hanna; Yuyun, Ignasia; Pattiwael, Athriyana S.; Mau, Emanuella C. Natalia (Journal of ELT Research, 2019)
Student-centered learning has been the new trend in education field in recent years. Various levels of education have started to gradually shift their teaching approach from the traditional teacher-centered instruction into student-centered instruction. This transition that focuses the learning process on students is considered desirable by society as it offers various benefits for students’ personal and academic growth (Clifford, 1999). However, in higher education, where most teaching instructions are naturally conducted in the form of lectures, the application of student-centered approach may appear as unfamiliar to students who are used to teacher-centered instruction. This study, hence, aims to investigate how undergraduate students responded to a shift in their classroom instruction, from teacher-centered into student-centered. An action research was conducted in three meetings of a Reading and Writing course for EFL undergraduate students in the Department of English. The study collected the data from class observations done by three observers. The field notes, observation reports, and discussion notes resulted from the three observation sessions were then analyzed using a qualitative approach to find out the students’ responses towards the student-centered classroom instructions. The findings of this study reveal that most of the students responded positively towards the student-centered instruction, as shown in their active involvement during the learning activities, such as in pair works, group discussions, and collaborative work using technology. The implications and recommendations drawn from this study are discussed in the paper.